2010
DOI: 10.1021/jf903004a
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Selenium Speciation Associated with Increasing Tissue Concentrations of Selenium in Wheat Grain

Abstract: Wheat (Triticum aestivum) collected in the Nawanshahr-Hoshiarpur Region (Punjab, India) showed the highest selenium concentrations ever recorded in cereal grains (29-185 microg g(-1)). There was a strong positive relationship between the selenium content in shoots and that in kernels, showing that grain selenium concentration can be predicted from that in the vegetative tissues of the plant. The identity and content of the selenocompounds in the grain samples and in wheat-based reference materials were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 27 publications
9
83
0
Order By: Relevance
“…As shown in Table 3, SeMet was the major Se species found in all samples, which is in agreement with Cubadda et al (2010) and Hart et al (2011), who have stated that about 75 and 60 %, respectively, of the total Se present in wheat flour is in the form of SeMet. Even if the matrix material of our samples cannot be strictly viewed as typical (commercial) wheat flour, 70 to 100 % of their total Se is in the form of SeMet.…”
Section: Selenium Speciationsupporting
confidence: 88%
“…As shown in Table 3, SeMet was the major Se species found in all samples, which is in agreement with Cubadda et al (2010) and Hart et al (2011), who have stated that about 75 and 60 %, respectively, of the total Se present in wheat flour is in the form of SeMet. Even if the matrix material of our samples cannot be strictly viewed as typical (commercial) wheat flour, 70 to 100 % of their total Se is in the form of SeMet.…”
Section: Selenium Speciationsupporting
confidence: 88%
“…The Se concentrations of the samples investigated in this study appear to be the highest ever recorded in cereal grains for human consumption, similar to wheat reported earlier by our group (Cubadda et al, 2010;Sharma et al, 2009). These levels of intake might be leading to chronic toxic effects of Se accumulation in human through Se-rich food grains and livestock fed on rice and maize straw as fodder.…”
Section: Resultssupporting
confidence: 90%
“…The uncertainties quoted in Table 1 are the standard deviations at + 1 s confidence limits obtained from three independent sample analyses and the percentage relative standard deviations are in the range of 1.5-5%. INAA quantification of Se in cereal grains, as reported by this group (Sharma et al, 2009), was found to agree with quantification by ICP-MS in the case of wheat (Cubadda et al, 2010).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations